Sistemas de manejo de um Argissolo dos tabuleiros costeiros de Sergipe cultivado com citros - Anjos, Joézio Luiz dos (2006)
In spite the social and economic importance of citrus on tablelands ecossistem in Northeasten Brazil, specially in Sergipe and Bahia States, the citrus yield is yet very lowone box of 40,8 kg per tree. Among the restrictive factors to the business of Sergipe citrus area, the second most important in Brazil, are outstanding those related to physical and chemical characteristics of the tableland soils – high acidity, low natural fertility and mainly the coercion layers located near by the soil surface. These pedogenetic layers are typical in tableland soils and cause noticeable limitation to soil water and to root system of trees. Doing interrow tillages based in intensive utilization of agricultural machines chiefly harrows, the growers of that region give contribution to increase negative effects of handsettings, resulting in modification in the physical and hydric soil qualities, impairing its fertility and then the grove productivity. The aim of this study was the evaluate hydric and physic properties of the soil under different tillage systems in the interrows to control weeds. The treatments were as follow: 1) Subsoiling and harrowing all over the year; 2) No subsbsoiling and harrowing all over the year. 3) Mowing in the rainy season (From April to September) and harrowing in the dry season (October to March) with subsoiling. 4) Mowing in rainy season and harrowing in the dry one without subsoiling; 5) Intercropping of jackbean (Canavalia ensiformis D.C.) in the rainy season and harrowing in the dry one with subsoiling; .6) Intercropping of jackbean in rainy season and harrowing in dry one without subsoiling. The experiment design was a split-plot randomized block with the treatments as plots and subsoiling depth as subplots. The assay was set for in field early in 1994 in a citrus orchard (Pera orange Citrus sinensis, Osbeck on ‘Rangpure’ lime C. limonia, Osbeck.) and the physical soil properties were assessed in 2003. By the result it was concluded that the tillage systems green cover, mowing and subsoiling alone or associated with Canavalia ensiformes, D.C.- promoted important beneficial modification in the physical and hydric attributes evaluated. It was observed that 80% of the roots were at 0-30 cm in deph and 63% were at 20 cm.The lateral root distribution was 80% corresponding at plant canopy. The combination C. ensiformis and subsoiling tended to result longer and deeper in depth citrus roots.